Oncogenic KRAS suppresses store-operated Ca2+ entry and ICRAC through ERK pathway-dependent remodelling of STIM expression in colorectal cancer cell lines. (June 2018) - Pierro, Cristina; Zhang, Xuexin; Kankeu, Cynthia; Trebak, Mohamed; Bootman, Martin D.; Roderick, H. Llewelyn
Graphical abstract: Highlights: Oncogenic KRAS suppresses SOCE/ICRAC in colorectal cancer cell (CRC) lines. STIM expression is remodelled in CRCs following oncogenic KRAS deletion. STIM1 re-expression is sufficient to rescue SOCE in CRCs. STIM1 expression is regulated by the MEK/ERK pathway in CRCs. Abstract: The KRAS GTPase plays a fundamental role in transducing signals from plasma membrane growth factor receptors to downstream signalling pathways controlling cell proliferation, survival and migration. Activating KRAS mutations are found in 20% of all cancers and in up to 40% of colorectal cancers, where they contribute to dysregulation of cell processes underlying oncogenic transformation. Multiple KRAS-regulated cell functions are also influenced by changes in intracellular Ca 2+ levels that are concurrently modified by receptor signalling pathways. Suppression of intracellular Ca 2+ release mechanisms can confer a survival advantage in cancer cells, and changes in Ca 2+ entry across the plasma membrane modulate cell migration and proliferation. However, inconsistent remodelling of Ca 2+ influx and its signalling role has been reported in studies of transformed cells. To isolate the interaction between altered Ca 2+ handling and mutated KRAS in colorectal cancer, we have previously employed isogenic cell line pairs, differing by the presence of an oncogenic KRAS allele (encoding KRAS G13D ), and have shown that reduced Ca 2+ release from the ER and mitochondrial Ca 2+ uptake contributes to the survival advantage conferred by oncogenic KRAS. Here we show in the same cell lines, that Store-Operated Ca 2+ Entry (SOCE) and its underlying current, ICRAC are under the influence of KRAS G13D . Specifically, deletion of the oncogenic KRAS allele resulted in enhanced STIM1 expression and greater Ca 2+ influx. Consistent with the role of KRAS in the activation of the ERK pathway, MEK inhibition in cells with KRAS G13D resulted in increased STIM1 expression. Further, ectopic expression of STIM1 in HCT 116 cells (which express KRAS G13D ) rescued SOCE, demonstrating a fundamental role of STIM1 in suppression of Ca 2+ entry downstream of KRAS G13D . These results add to the understanding of how ERK controls cancer cell physiology and highlight STIM1 as an important biomarker in cancerogenesis.